Energy Liberation in the Flow of Fluid inside the Circular Couette System with Opposed Rotation of Cylinders - A.F. Serov; V.N. Mamonov; A.D. Nazarov (Учёные записки Казанского университета: Серия Физико-математические науки)
The paper presents the design of a heat generator intended for efficient conversion of kinetic wind energy into thermal energy. The design is based on the circulation of the viscous working liquid in the system of cylindrical ring channels, which are formed by the “rotors” rotating opposite (towards) to each other. The results of experiments on measuring the heat capacity of heat generators in different operational modes are presented. The analysis of the obtained results is carried out.